2020
DOI: 10.1097/md.0000000000022115
|View full text |Cite
|
Sign up to set email alerts
|

Arterial resection during pancreatectomy for pancreatic ductal adenocarcinoma with arterial invasion

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 40 publications
1
19
0
1
Order By: Relevance
“…Recently, an increasing number of major peripancreatic arterial resections for locally advanced PC, as defined by the NCCN criteria (Version 1.2020, 11/26/19), especially after NAC, are being reported [14] , [20] , [21] , [22] , [23] . Among them, CAR has gained the most interest [1] , [2] , [10] , [13] , [15] , [18] , [24] , although, it is still rarely performed, even in well-established pancreatic centers, where the annual number of CARs varies between 0.4 and 3.8 [1] , [2] , [13] , [16] .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an increasing number of major peripancreatic arterial resections for locally advanced PC, as defined by the NCCN criteria (Version 1.2020, 11/26/19), especially after NAC, are being reported [14] , [20] , [21] , [22] , [23] . Among them, CAR has gained the most interest [1] , [2] , [10] , [13] , [15] , [18] , [24] , although, it is still rarely performed, even in well-established pancreatic centers, where the annual number of CARs varies between 0.4 and 3.8 [1] , [2] , [13] , [16] .…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, Kwon et al [ 63 ] published a study conducted on 109 PDAC patients undergoing pancreatectomy with AR between 2000 and 2017. Among 109 patients, 38 underwent surgery after neoadjuvant chemotherapy, and 71 underwent upfront surgery.…”
Section: Arterial Resectionsmentioning
confidence: 99%
“…The authors concluded that pancreatectomy with AR can be an acceptable procedure in terms of postoperative morbidity and mortality in highly selected patients. Additionally, the survival benefit was noted in patients who were undergoing neoadjuvant chemotherapy compared with patients undergoing upfront surgery [ 63 ].…”
Section: Arterial Resectionsmentioning
confidence: 99%
“…With neoadjuvant FOLFIRINOX ( 4 6 ) combined arterial or major venous resection ( 7 , 8 ) applied to borderline resectable pancreatic cancer (BRPC) and locally advanced pancreatic cancer (LAPC), the overall radical resection rate of pancreatic cancer has been improved to some extent. With the rapid spread of standardized surgical procedures for pancreatic cancer and the optimization of perioperative patient management, increasing evidence supports pancreatic surgery combined with arteriovenous resection and reconstruction for LAPC patients with encouraging short-term and long-term prognoses ( 9 11 ).…”
Section: Introductionmentioning
confidence: 99%